2018
DOI: 10.3390/molecules23030581
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Targeted Alpha-Particle Therapy. What We Learned about Recoils Release from In Vivo Generators

Abstract: This review summarizes recent progress and developments as well as the most important pitfalls in targeted alpha-particle therapy, covering single alpha-particle emitters as well as in vivo alpha-particle generators. It discusses the production of radionuclides like 211At, 223Ra, 225Ac/213Bi, labelling and delivery employing various targeting vectors (small molecules, chelators for alpha-emitting nuclides and their biomolecular targets as well as nanocarriers), general radiopharmaceutical issues, preclinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 91 publications
1
84
0
Order By: Relevance
“…Deep understanding of the surface properties of HAp and TiO 2 nanoparticles, as prospective carriers for targeted alpha-particle therapy by in vivo generators, is important. 18 The results will allow us to predict and provide further evaluation of kinetics and sorption dependences of various ions and radionuclides, including 223 Ra and its decay products which are present in the form of cations. Therefore, the studied nanoparticles, which are capable of both capture and resorption, due to their high capacity and suitable size, are a promising solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep understanding of the surface properties of HAp and TiO 2 nanoparticles, as prospective carriers for targeted alpha-particle therapy by in vivo generators, is important. 18 The results will allow us to predict and provide further evaluation of kinetics and sorption dependences of various ions and radionuclides, including 223 Ra and its decay products which are present in the form of cations. Therefore, the studied nanoparticles, which are capable of both capture and resorption, due to their high capacity and suitable size, are a promising solution.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, nanoparticles can be targeted to cancer by both passive and active mechanisms, due to the EPR effect or functionalization of the surface. 18 Nanohydroxyapatite and nTiO 2 were chosen for this purpose because these materials are already widely used in medicine and cosmetics. They are stable, nontoxic, biocompatible, cheap, and easy to prepare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell survival studies have shown that in contrast to β − -radiation, α particle-killed cells independently of their oxygenation state, cell cycle position or fluency [124]. Due to these advantages, targeted α-particle therapy is the most rapidly developing field in nuclear medicine and radiopharmacy [125]. Unfortunately in the case of radionuclides such as 225 Ac, 227 Th and 223 Ra the daughter products are also α-emitters or β-emitters, and these radionuclides not remain complexed to chelators since they represent elements with different chemistry.…”
Section: α-Emitting Radionuclidesmentioning
confidence: 99%
“…The renal toxicity induced by longer-lived decay product 213 Bi is considered to be the major constraint to apply 225 Ac in tumor therapy [128,129]. A review publication broadly describing recoil problem has been recently published by Kozempel et al [125]. Several α emitters have been investigated so far for targeted prostate cancer immunotherapy: bismuth-213 [130,131], actinium-225 [125,132], astatine-211 [133], radium-223 [134,135], thorium-227 [136] and lead-212 [137] (Table 1).…”
Section: α-Emitting Radionuclidesmentioning
confidence: 99%